Sulfate erosion resistant agent and preparation method thereof

By using modified expanded graphene inorganic salts to destroy the sulfate structure, a sulfate erosion agent was prepared, which solved the problems of complex formulation and difficult preparation process in the prior art, and achieved efficient sulfate erosion effect and industrial application potential.

CN119612997APending Publication Date: 2025-03-14SHAANXI KZJ NEW MATERIALS +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411795366.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing sulfate erosion agent has complex formulations, difficult preparation processes or limited performance improvements in certain specific materials, making it difficult to adapt to a variety of complex environments and industrial applications.

Method used

Modified expanded graphene inorganic salt is used as the main component, and a sulfate anti-corrosion agent is prepared by the adsorption of graphite and the reaction between the inorganic salt and the sulfate salt. The corrosion-resistant agent includes 50 parts of modified expanded graphene inorganic salt, 20 parts of cement and 30 parts of mineral blend. The doping amount is appropriately adjusted according to the different sulfate concentration in the environment.

Benefits of technology

It effectively reduces the erosion of sulfates on concrete, improves the sulfate corrosion resistance of concrete, and has relatively simple preparation process and has industrial potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a sulfate corrosion resistant agent and a preparation method thereof, and the sulfate corrosion resistant agent comprises the following components in parts by weight: a modified expanded graphene inorganic salt component; a cement clinker component; and an admixture component. Wherein the modified expanded graphene inorganic salt is obtained by modifying expandable graphite with inorganic salt. The modified expanded graphene inorganic salt is introduced into the sulfate corrosion resistant agent, and the modified expanded graphene inorganic salt effectively reduces the corrosion effect of sulfate on concrete through the adsorption effect of graphite and the combined effect that the inorganic salt reacts with sulfate to destroy the sulfate structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete admixtures, in particular to an anti-sulfate corrosion agent and a preparation method thereof. Background Art

[0002] In recent years, sulfate corrosion of concrete has become a major challenge to the durability of concrete structures in my country, especially in important projects such as roads and bridges. This corrosion has significant regional characteristics. The salt lake areas in western my country and the sulfate soil areas in southern China, as well as the sulfate-containing seawater environment in the coastal areas, have all led to severe corrosion and premature failure of concrete structures, threatening the life and safety of the structures.

[0003] Since the 1950s, my country has begun to pay attention to the problem of sulfate corrosion of concrete and has accumulated relevant test data and research results. For example, the research on the mechanism of sulfate corrosion and its accelerated experiment by the China Academy of Building Research has provided an important reference for solving the problem of sulfate corrosion of concrete. In recent years, both at home and abroad, the ability of concrete to resist sulfate corrosion and its durability has been improved by adding mineral admixtures (such as fly ash, silica fume, and mineral powder). However, the existing technology still has some limitations, such as limited anti-corrosion effect or complex preparation process, and difficulty in industrial application.

[0004] Among the relevant technologies at home and abroad, some patents provide solutions to resist sulfate erosion, but there is still a certain gap between the technical characteristics and actual needs.

[0005] For example, patent AU528193B2 improves the corrosion resistance of concrete by introducing calcium nitrite and water reducing agent;

[0006] Patent CN101781100A uses ultra-fine fly ash microspheres and expansion agents to prepare anti-corrosion agents;

[0007] Patent CN115974447A proposes to use modified red mud to synergize with other components to improve the corrosion resistance of concrete;

[0008] Patent CN101792279A significantly improves the durability of concrete through a mixture of various nitrates and fly ash.

[0009] However, these technologies often have problems such as complex formulas, difficult preparation processes, or limited performance improvements on certain specific materials.

[0010] In summary, although the existing technology has made certain progress in improving the sulfate corrosion resistance of concrete, it is still necessary to further develop new sulfate corrosion-resistant materials or solutions that can adapt to a variety of complex environments, have simple preparation processes and have industrial potential to meet current and future engineering needs. Summary of the invention

[0011] Based on this, it is necessary to provide an anti-sulfate corrosion agent to solve the problems of complex formula, difficult preparation process or limited performance improvement of certain specific materials in the anti-sulfate corrosion agent in the prior art.

[0012] To achieve the above object, the present invention provides a technical solution:

[0013] An anti-sulfate corrosion agent, comprising, by weight:

[0014] 50 parts of modified expanded graphene inorganic salt;

[0015] 20 parts of cement; and

[0016] 30 parts of mineral admixture;

[0017] Wherein, the modified expanded graphene inorganic salt is obtained by modifying expandable graphite with an inorganic salt.

[0018] Preferably, the preparation steps of the modified expanded graphene inorganic salt are as follows:

[0019] Expanding the expandable graphene under the action of microwaves with a power of 300 to 1000 W to obtain expanded expandable graphene;

[0020] Adding an inorganic salt aqueous solution to the expanded expandable graphene, and obtaining an expanded graphene inorganic salt sample after the expanded graphene is adsorbed to saturation;

[0021] The expanded graphene inorganic salt sample is dried and crushed in an oven to prepare a modified expanded graphene inorganic salt sample.

[0022] Preferably, the expansion time is 3 min to 5 min.

[0023] Preferably, the mass concentration of the inorganic salt aqueous solution is 40% to 60%.

[0024] Preferably, the inorganic salt is a cationic metal salt formed by combining a metal cation with a non-sulfate anion.

[0025] Preferably, the metal cations include at least one of calcium ions, barium ions, lead ions, mercury ions and silver ions.

[0026] Preferably, the non-sulfate anion includes at least one of nitrite ion, nitrate ion, bromate ion and acetate ion.

[0027] Preferably, the cement clinker includes at least one of silicate cement clinker, sulphoaluminate cement clinker and high sulfate-resistant cement clinker.

[0028] Preferably, the mineral admixture includes at least one of silica fume, fly ash and slag powder.

[0029] The present invention also provides a method for preparing an anti-sulfate corrosion agent, comprising the steps of:

[0030] The modified expanded graphene inorganic salt, the cement clinker and the mineral admixture are uniformly mixed to obtain the anti-sulfate corrosion agent.

[0031] When sulfate corrosion inhibitors are applied to concrete, the dosage of the anti-sulfate corrosion inhibitors used varies according to the sulfate concentration in the environment;

[0032] When the sulfate concentration in the environment is less than 500 mg / L, the amount of anti-sulfate corrosion agent added is 1.0-3.0% of the amount of rubber material;

[0033] When the sulfate concentration in the environment is between 500mg / L and 6000mg / L, the dosage is 3.0-8.0% of the amount of the rubber material;

[0034] When the sulfate concentration in the environment is greater than 6000 mg / L, the dosage is 8.0-12.0% of the amount of the rubber material.

[0035] Beneficial effects of the present invention:

[0036] The invention introduces modified expanded graphene inorganic salt into the sulfate corrosion resistance agent. The modified expanded graphene inorganic salt effectively reduces the corrosion of sulfate on concrete through the adsorption of graphite and the combined effect of the inorganic salt and sulfate reaction to destroy the sulfate structure. DETAILED DESCRIPTION

[0037] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0038] In the examples, the test methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0039] An anti-sulfate corrosion agent, comprising, by weight:

[0040] 50 parts of modified expanded graphene inorganic salt;

[0041] 20 parts of cement; and

[0042] 30 parts of mineral admixture;

[0043] Wherein, the modified expanded graphene inorganic salt is obtained by modifying expandable graphite with an inorganic salt.

[0044] In some embodiments, the preparation steps of the modified expanded graphene inorganic salt are as follows:

[0045] Expanding the expandable graphene under the action of microwaves with a power of 300 to 1000 W to obtain expanded expandable graphene;

[0046] Adding an inorganic salt aqueous solution to the expanded expandable graphene, and obtaining an expanded graphene inorganic salt sample after the expanded graphene is adsorbed to saturation;

[0047] The expanded graphene inorganic salt sample is dried and crushed in an oven to prepare a modified expanded graphene inorganic salt sample.

[0048] In some embodiments, the expansion time is 3 min to 5 min.

[0049] In some embodiments, the mass concentration of the inorganic salt aqueous solution is 40% to 60%.

[0050] In some embodiments, the inorganic salt is a cationic metal salt formed by combining a metal cation with a non-sulfate anion.

[0051] In some embodiments, the metal cations include at least one of calcium ions, barium ions, lead ions, mercury ions, and silver ions.

[0052] In some embodiments, the non-sulfate anion includes at least one of a nitrite ion, a nitrate ion, a bromate ion, and an acetate ion.

[0053] In some embodiments, the cement clinker includes at least one of silicate cement clinker, sulfoaluminate cement clinker and high sulfate-resistant cement clinker.

[0054] In some embodiments, the mineral admixture includes at least one of silica fume, fly ash, and slag powder.

[0055] The present invention also provides a method for preparing an anti-sulfate corrosion agent, comprising the steps of:

[0056] The modified expanded graphene inorganic salt, the cement clinker and the mineral admixture are uniformly mixed to obtain the anti-sulfate corrosion agent.

[0057] When sulfate corrosion inhibitors are applied to concrete, the dosage of the anti-sulfate corrosion inhibitors used varies according to the sulfate concentration in the environment;

[0058] When the sulfate concentration in the environment is less than 500 mg / L, the amount of anti-sulfate corrosion agent added is 1.0-3.0% of the amount of rubber material;

[0059] When the sulfate concentration in the environment is between 500mg / L and 6000mg / L, the dosage is 3.0-8.0% of the amount of the rubber material;

[0060] When the sulfate concentration in the environment is greater than 6000 mg / L, the dosage is 8.0-12.0% of the amount of the rubber material.

[0061] Example 1

[0062] 1. Preparation of modified expanded graphene inorganic salt:

[0063] Calcium nitrate and water are mixed to prepare a 50 wt.% aqueous solution for standby use;

[0064] 100 parts of expandable graphene were exposed to 400 W microwave power for 3 minutes, and then placed in a beaker. The prepared calcium nitrate solution was then added dropwise onto the expanded graphene until the graphene was saturated with adsorption (about 60 parts of calcium nitrate solution was sufficient for saturation).

[0065] The saturated expanded graphene calcium nitrate is dried in an oven and crushed into powder by a pulverizer to obtain a modified expanded graphene salt.

[0066] 2. Preparation of anti-sulfate corrosion agent:

[0067] 50 parts of the modified expanded graphene salt are uniformly mixed with 20 parts of ordinary Portland cement clinker and 30 parts of fly ash as fillers to finally prepare the concrete anti-sulfate corrosion agent described in this patent.

[0068] Example 2

[0069] 1. Preparation of modified expanded graphene inorganic salt:

[0070] Prepare a 50 wt.% aqueous solution with silver nitrate and water for later use;

[0071] 100 parts of expandable graphene were exposed to 600W microwave power for 3 minutes, and then placed in a beaker. The prepared silver nitrate solution was then added dropwise onto the expanded graphene until the graphene was saturated with adsorption (about 80 parts of silver nitrate solution was sufficient for saturation).

[0072] The saturated expanded graphene silver nitrate is dried in an oven and crushed into powder by a pulverizer to obtain a modified expanded graphene salt.

[0073] 2. Preparation of anti-sulfate corrosion agent:

[0074] 60 parts of the modified expanded graphene salt are uniformly mixed with 20 parts of high sulfate-resistant cement clinker and 20 parts of mineral powder as fillers to finally prepare the concrete anti-sulfate corrosion agent described in this patent.

[0075] Example 3

[0076] 1. Preparation of modified expanded graphene inorganic salt:

[0077] Calcium bromate and water are mixed to prepare a 50 wt.% aqueous solution for standby use;

[0078] 100 parts of expandable graphene were exposed to 500 W microwave power for 4 minutes, and then placed in a beaker. The prepared calcium bromate solution was then added dropwise onto the expanded graphene until the graphene was saturated with adsorption (about 70 parts of calcium bromate solution were sufficient for saturation).

[0079] The saturated expanded graphene calcium bromate is dried in an oven and crushed into powder by a pulverizer to obtain a modified expanded graphene salt.

[0080] 2. Preparation of anti-sulfate corrosion agent:

[0081] 55 parts of the modified expanded graphene salt are mixed evenly with 20 parts of high sulfate-resistant cement clinker and 25 parts of silica fume as fillers to finally prepare the concrete anti-sulfate corrosion agent described in this patent.

[0082] Comparative Example 1

[0083] The other steps are the same as those in Example 1, except that:

[0084] The step of preparing the modified expanded graphene inorganic salt is not included. In the step of preparing the anti-sulfate corrosion agent, the modified expanded graphene salt is replaced with an equal amount of expandable graphene.

[0085] Comparative Example 2

[0086] The other steps are the same as those in Example 1, except that:

[0087] Excluding the step of preparing the modified expanded graphene inorganic salt, in the step of preparing the anti-sulfate corrosion agent, the modified expanded graphene salt is replaced by an equal amount of calcium nitrate.

[0088] Comparative Example 3

[0089] Youbaowan A15 anti-sulfate corrosion agent is sold in Xinjiang market.

[0090] Comparative Example 4

[0091] The other steps are the same as those in Example 1, except that:

[0092] The step of preparing the modified expanded graphene inorganic salt is not included. In the step of preparing the anti-sulfate corrosion agent, the modified expanded graphene salt is replaced by an equal amount of ordinary Portland cement.

[0093] The concrete anti-sulfate corrosion preservatives of Examples 1, 2, 3 and Comparative Examples 1, 2, 3, and 4 were tested in accordance with the test method specified in the industry standard JC / T 1011-2021 "Concrete Anti-Corrosion Preservatives" and tested for relevant properties at a dosage of 6%. The test results are shown in Table 1.

[0094] Table 1 Performance test results

[0095]

[0096] Note: The compressive strength ratio in the table refers to the strength ratio of the mortar test block mixed with anti-sulfur preservatives and the benchmark test block without anti-sulfur preservatives.

[0097] All indicators of data examples 1, 2, and 3 in the table meet the standard requirements;

[0098] Comparative Example 1: Since only expanded graphene is added in Comparative Example 1, and the expanded graphene is not filled with an inorganic salt solution, it is difficult for the sulfate in the concrete to be quickly and efficiently filled in the expanded graphene, resulting in aggravated sulfate erosion, a low corrosion resistance coefficient, and a higher expansion rate and expansion coefficient due to sulfate erosion and expansion. The 28d compressive strength ratio is low, and the final sample 28d compressive strength ratio, 28d expansion rate, expansion coefficient, and corrosion resistance coefficient do not meet the standard requirements;

[0099] Comparative Example 2: Since only inorganic salts were added in Comparative Example 2, and the salt-modified graphene was not used as the core material, the insoluble substances generated by the reaction of the inorganic salts with sulfates in the environment could not be adsorbed by the expanded graphene. The insoluble substances finally generated expanded in the concrete structure, resulting in a high 28d expansion rate and expansion coefficient, and a decreased corrosion resistance coefficient. The final sample's 28d expansion rate, expansion coefficient, and corrosion resistance coefficient did not meet the standard requirements;

[0100] Comparative Example 3: The 28d compressive strength ratio and 28d expansion ratio do not meet the standard requirements. Although the corrosion resistance coefficient meets the standard requirements, it is nearly 20% lower than that of Examples 1, 2, and 3.

[0101] Comparative Example 4: In Comparative Example 4, there is no modified graphene inorganic salt, but cement is used instead. Therefore, it has no relevant anti-corrosion and anti-corrosion effect from the mechanism. The concrete structure is corroded by sulfate in the environment, and the concrete structure expands and cracks. The anti-corrosion coefficient does not meet the standard. Therefore, its 28d expansion rate, expansion coefficient, and anti-corrosion coefficient do not meet the standard requirements.

[0102] It should be noted that the specific parameters or some reagents in the above embodiments are specific embodiments or preferred embodiments of the present invention, rather than limiting the present invention; those skilled in the art can make adaptive adjustments within the scope of the present invention.

Claims

1. A sulfate corrosion inhibitor, characterized in that: In parts by weight, it includes: 40-70 parts of modified expanded graphene inorganic salt; 15-25 parts of cement clinker; and 15-35 parts of mineral admixture; Wherein, the modified expanded graphene inorganic salt is obtained by modifying expandable graphene with an inorganic salt.

2. The anti-sulfate corrosion agent according to claim 1, characterized in that: The preparation steps of the modified expanded graphene inorganic salt are as follows: Expanding the expandable graphene under the action of microwaves with a power of 300 to 1000 W to obtain expanded expandable graphene; Adding an inorganic salt aqueous solution to the expanded expandable graphene, and obtaining an expanded graphene inorganic salt sample after the expanded graphene is adsorbed to saturation; The expanded graphene inorganic salt sample is dried and crushed in an oven to prepare a modified expanded graphene inorganic salt sample.

3. The anti-sulfate corrosion agent according to claim 2, characterized in that: The expansion time is 3min to 5min.

4. The anti-sulfate corrosion agent according to claim 2, characterized in that: The mass concentration of the inorganic salt aqueous solution is 40% to 60%.

5. The anti-sulfate corrosion agent according to claim 1, characterized in that: The inorganic salt is a cationic metal salt formed by combining a metal cation with a non-sulfate anion.

6. The anti-sulfate corrosion agent according to claim 5, characterized in that: The metal cations include at least one of calcium ions, barium ions, lead ions, mercury ions, and silver ions.

7. The anti-sulfate corrosion agent according to claim 5, characterized in that: The non-sulfate anion includes at least one of a nitrite ion, a nitrate ion, a bromate ion, and an acetate ion.

8. The anti-sulfate corrosion agent according to claim 1, characterized in that: The cement clinker includes at least one of silicate cement clinker, sulphoaluminate cement clinker and high sulfate resistance cement clinker.

9. The anti-sulfate corrosion agent according to claim 1, characterized in that: The mineral admixture includes at least one of silica fume, fly ash and slag powder.

10. A method for preparing the anti-sulfate corrosion agent according to any one of claims 1 to 9, characterized in that: Includes steps: The modified expanded graphene inorganic salt, the cement clinker and the mineral admixture are uniformly mixed to obtain the anti-sulfate corrosion agent.

Citation Information

Patent Citations

  • Anti-erosion agent for concrete, preparation method and application thereof

    CN101781100A

  • Formula and preparation process of concrete sulfate resistance agent

    CN101792279A